Carbon isotopic analysis of reactive organic matter using a new pyrolysis-cryotrapping-isotope ratio mass spectrometry method: The isotope variation of organic matter within the S1 and S2 peaks of Rock-Eval. (October 2019) - Dörner, M.; Berner, U.; Erdmann, M.; Barth, T.
Highlights: Introduction of a new online pyrolysis carbon isotope analysis method. Case study of sample material from different locations and depositional environments. Isotopic fractionation curves are related to depositional environment and maturity. Maturity is reflected in the carbon isotopic difference of the Rock-Eval S1 and S2. Abstract: The source material, the mode of photosynthesis, the organic matter (OM) type, the paleoenvironmental conditions and thermal degradation all determine the isotopic composition of OM. This study presents a novel analytical technique and demonstrates its potential to enhance the understanding of the preservation and maturation-related isotopic compositional changes in OM from different paleoenvironments. A new Rock-Eval type pyrolysis coupled to isotope ratio mass spectrometry (py-IRMS) method has been developed to monitor the isotopic changes during Rock-Eval type pyrolysis while simultaneously recording pyrograms to obtain S1 and S2 peaks compatible with standard Rock-Eval pyrolysis. An automated cryotrapping method allows the sequential sampling of product from defined pyrolysis portions. Each subsample is subsequently transferred to the isotopic ratio mass spectrometer for carbon isotopic measurements. In addition, the cryotrap serves to focus sample peaks, enabling robust and reproducible results even at standard Rock-Eval heating rates. In combination with a standard elemental analyser coupled to an isotopic ratio mass spectrometer (EA–IRMS) it was possible to deconvolute the carbon isotope composition of the reactive components, bitumen and inert components of OM. This allowed us to observe depositional control as well as changes imposed by maturation. Our initial results show the potential of the proposed isotopic screening method to deduce a variety of organic geochemical properties of different OM types based on differences in their carbon isotope compositions. Our results suggest that the ability to produce significant isotopic fractionation during the proposed pyrolysis method is highly dependent on the preservation state of the OM and the thermal maturity.